Engaging Minds: The Effectiveness of Illustrated Story Handouts in Teaching Chemical Bonding - Rokhmayanti, Rokhmayanti; Fauzi, Bahrul (Journal of Chemical Learning Innovation, 2025)
Purpose of the study: This study aims to determine whether there is an increase in the motivation to learn chemistry of class X3 students of YLPI Marpoyan Senior High School, Bukit Raya District, Pekanbaru City through the use of handouts in the form of illustrated stories. Methodology: The instruments used in this study are observation and documentation. Observation is done to find out the development of teachers and students in the learning process. While documentation is done to obtain school data, teacher data, and also student data. Main Findings: Based on the results of data analysis, the percentage of student motivation before the action was 49.4%, cycle I 53.8%, cycle II 60.9%, and cycle III 76.4%, which increased at each meeting, so it can be concluded that the use of handouts in the form of illustrated stories can increase student learning motivation. Novelty/Originality of this study: The novelty of this study is to determine the effectiveness of using handouts in the form of illustrated stories to increase students' learning motivation on the topic of chemical bonds.